The Role of Bank Muamalat Indonesia KCP Kepanjen in Determining Customer Decisions Using Hajj Program Financing Products (Prohajj) with the Qardh Wakalah Bil Ujrah Agreement - Nurwakhidah, Ana; Musfiroh , Ulil Mayasari (Danadyaksa: Post Modern Economy Journal, 2024)
In addition to learning more about the hajj program financing products offered by Bank Muamalat Indonesia KCP Kepanjen, the purpose of this service activity is to ascertain how the Qardh Wakalah bil Ujrah contract is applied to those products. where Muslims make up the majority of the Indonesian population. This is evident from the enthusiasm of Indonesian Muslims in response to the KMA No. 189 of 2023 decree concerning Indonesian Hajj Quotas for 1444 H/2023 M totaling 221,000, consisting of 203,320 regular haj Quotas and 17,680 special Hajj Quotas, which was signed by the Minister of Religion Yaqut Cholil Qoumas. Then one of Islamic banking's functions is to offer Hajj program services that can facilitate Muslims' ability to execute the pilgrimage. This writing uses a descriptive qualitative method, the author describes the object of research by recording, observing, and interviewing all matters related to this research and aligning it with primary and secondary data sources. The respondent from this writing is the Relationship Manager of Bank Muamalat Indonesia KCP Kepanjen. observation directly or indirectly on the object under study as well as data collection with related documents. The results of this study indicate that the Hajj financing product at Bank Muamalat Indonesia in KCP Kepanjen uses the Qardh Wakalah Bil Ujrah contract, namely funds lent by the bank to prospective hajj customers.